A new phase of European integration. Organized capitalisms in post-ricardian Europe - Höpner, Martin; Schäfer, Armin (Köln, 2007)
"In the past, economic integration in Europe was largely compatible with the persistence of different national varieties of capitalism. While product market integration intensified competition, member states could build on and foster their respective comparative advantage. To date, this no longer unequivocally holds true. We contend that a new, 'Post-Ricardian' phase of European integration has emerged in which the Commission's and the ECJ's attempts to further economic integration systematically challenge the institutions of organized capitalism. This quest for liberalization has reached a point at which its output legitimacy is increasingly uncertain. As a result, the de-politicization of EU decisions proves increasingly unsuccessful. In addition, liberalization measures rely on a very generous interpretations of the 'four freedoms' that exceeds the amount of liberalization the member states agreed upon in the European treaties and, therefore, lacks input legitimacy. We show this by discussing recent struggles over the Services Directive, the Takeover Directive, and company law. In the current phase of European integration, the Commission's and the ECJ's liberalization attempts either transform the institutional foundations on which some of the member states' economic systems rely or they create political resistance to an extent that calls into question the European project. The case studies reveal evidence for both of these possibilities."